Festival Istiqlal sebagai Kesadaran Masyarakat dalam Membangun Islam Nusantara - Riza Dewi Al Ardi (Jurnal Al-Tatwir, 2021)
The chaotic life of Muslims in various parts of the world. This is important when Muslims are in a tough test. the problem of terrorism and radicalism in the name of religion. The challenges of globalization and modernization which are very aggressively spreading the "virus" throughout the social order inevitably bring about extraordinary changes in the order of human life. The sophistication of technology and the achievement of sophisticated inventions from the Western world are also challenges that must be answered by Muslim communities around the world. the decline in the quality of Muslim belief in Indonesia, due to a misunderstanding between religious and cultural education which seems to be contrary to the Shari'ah. Islam came to Indonesia directly from Arabia, to be precise Hadhramaut. To answer these accusations, as well as an effort to reaffirm Islam as a friendly and gracious religion (rahmatan lil alamin), requires deep socialization. With an exclusive approach to the community. Where the Istiqlal festival can be a da'wah land. Because at an event that is embellished with art, it will invite and build public awareness to return to having an Islamic understanding of the archipelago. So this research will discuss how the Istiqlal Festival can be a means for public awareness in building Islam Nusantara. The festival was attended by millions of people. No less than 7 million people attended the first Istiqlal Festival, as an exhibition that shows the spirit of Islam in various forms of Indonesian traditions, Fostering the same understanding on one commodity. 2. The Istiqlal Festival event was held for the first time at the Mamba'ul Ma'arif Islamic Boarding School (PP) Denanyar, Jombang. Bringing a positive impact with the unification of Muslims in Indonesia. From various circles to one. 3. It can be said as an arena for community development. Because the Istiqlal festival is under the auspices of major Islamic organizations in Indonesia.